Involvement of High-Conductance Calcium-Dependent Potassium Channels in Short-Term Presynaptic Plasticity in the Rat Dentate Gyrus - Baluchnejadmojarad, T.; Roghani, M. (Нейрофизиология, 2013)
We examined the involvement of high-conductance calcium-dependent potassium (BK) channels in short-term presynaptic plasticity in the rat dentate gyrus; a paired-pulse stimulation protocol was used for evaluation of this phenomenon. Paired-pulse responses were recorded from the dentate gyrus of rats while stimulating the medial part of the perforant path with different interpulse intervals (IPIs). Iberiotoxin (IbTX), a selective blocker of BK channels, at doses of 50 and 100 mg/kg was i.p. administered 30 min presurgery. The population spike (PS) amplitude ratio and field EPSP (fEPSP) amplitude and slope ratios were measured at IPIs 10, 20, 30, and 50 msec as indices of synaptic facilitation and/or depression. At IPIs of 10 and 20 msec, there was no significant increase in the PS amplitude ratio after IbTX. However, at longer IPIs (30 and 50 msec), there was a significant dose-dependent increase in this ratio vs the vehicle group (P < 0.05 and P < 0.01, respectively). There was a slight decrease in the fEPSP amplitude ratio at short IPIs (10, 20, and 30 msec) in rats pretreated with IbTX, while insignificant incrases in the fEPSP amplitude ratio were observed at longer IPIs (50 msec). With respect to the fEPSP slope ratio, IbTX dose-dependently and insignificantly increased it. In addition, longer IPIs did not provide significant changes in the fEPSP slope ratio. High-conductance calcium-dependent potassium channels in the rat dentate gyrus have a modulatory (inhibitory) and (apparently) regulatory role in short-term presynaptic plasticity at relatively long ISIs, and blocking of these channels leads to paired-pulse facilitation.